Prehistoric Perspectives on “Others” and “Strangers” - Belfer-Cohen, Anna; Hovers, Erella (Frontiers in Psychology, 2020)
Social ‘connectivity’ through time is currently considered as one of the major drivers of cultural transmission and cultural evolution. Within this framework, the interactions within-and between groups are impacted by individuals’ distinction of social relationships. In this paper, we focus on changes in one of the major aspects of social perceptions, ‘other’ and ‘stranger’, that took place in the course of the Pleistocene, as we infer them from the archaeological record. These changes would have occurred due to the plasticity of cognitive mechanisms, in response to the demands on behavior along the trajectory of human social evolution. The concepts of ‘other’ and ‘stranger’ have received little attention in the archaeological discourse, yet they are fundamental in the perception of social standing. The property of ‘otherness’ is defined by one’s perception and is inherent to one’s view of the world around oneself; when shared by a group it becomes a social cognitive construct. Allocating one the status of a ‘stranger’ is a socially-defined state that is potentially transient. We hypothesize that the latter is relatively a late addition to socio-cognitive categorization, associated with increased sedentism, larger groups and reduced territorial extent as part of the process of Neolithization. We posit that ‘others’ and ‘strangers’ can be approached from contextual archaeological data, with inferences as regards the evolution of cognitive social categories. Our analysis focused on raw material studies, observations on style and evidence for craft specialization. We find that contrary to the null hypothesis the archaeological record implies earlier emergence of complex socio-cognitive categorization. The cognitive, cultural and social processes involved in the maintenance and distinction between ‘others’ and ‘strangers’ can be defined as part of a process of ‘self-domestication’ that is still ongoing.